Histology, histochemistry and stereology of the adipose fin of Prochilodus lineatus - da Silva Alves, Rebeca Mamede [UNESP]; Pereira, Bruno Fiorelini [UNESP]; Pitol, Dimitrius Leonardo; Senhorini, Jose Algusto; Gimenes de Alcantara Rocha, Rita de Cassia; Caetano, Flávio Henrique [UNESP] (Wiley-Blackwell, 2012)
The adipose fin is small, nonpared, and usually located medially between the dorsal and caudal fin. Its taxonomic occurrence is very restrict; thus, it represents an important trace for taxon distinction. As it does not play a known vital physiological roll and it is easily removed, it is commonly used in marking and recapture studies. The present study characterizes the adipose fin of Prochilodus lineatus, as it is poorly explored by the literature. The adipose fin consists basically of a loose connective core, covered by a stratified epithelium supported by collagen fibers. At the epithelium, pigmented cells and alarm substance cells are found. Despite the name, adipocytes or lipid droplets are not observed on the structure of the fin. Microsc. Res. Tech., 2012. (c) 2011 Wiley Periodicals, Inc.
Keywords: adipose fin; Prochilodus lineatus; histochemistry